2006
DOI: 10.1037/0033-2909.132.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Does changing behavioral intentions engender behavior change? A meta-analysis of the experimental evidence.

Abstract: Numerous theories in social and health psychology assume that intentions cause behaviors. However, most tests of the intention- behavior relation involve correlational studies that preclude causal inferences. In order to determine whether changes in behavioral intention engender behavior change, participants should be assigned randomly to a treatment that significantly increases the strength of respective intentions relative to a control condition, and differences in subsequent behavior should be compared. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

125
2,247
9
34

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 3,024 publications
(2,415 citation statements)
references
References 168 publications
125
2,247
9
34
Order By: Relevance
“…reported medium to large effects between intention and behaviour, and self‐efficacy and behaviour, we found weak and inconsistent relationships between intention and behaviour, and self‐efficacy and behaviour in our studies. Our findings are compatible with the meta‐analysis by Webb and Sheeran (2006), which concluded that the link between intention and behaviour is much weaker than previously assumed (cf. Armitage & Conner, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…reported medium to large effects between intention and behaviour, and self‐efficacy and behaviour, we found weak and inconsistent relationships between intention and behaviour, and self‐efficacy and behaviour in our studies. Our findings are compatible with the meta‐analysis by Webb and Sheeran (2006), which concluded that the link between intention and behaviour is much weaker than previously assumed (cf. Armitage & Conner, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…All three health behaviours we examined are habitual; therefore, a question remains whether the same pattern of results would emerge for episodic health behaviours, such as screening and vaccination. Previous research has suggested that the impact of intentions may be diminished in habitual health behaviours (Ouellette & Wood, 1998; Webb & Sheeran, 2006). Therefore, future work should aim to further investigate the relationship between SES, intention, self‐efficacy, and health behaviours, using different examples of health behaviours, including episodic health behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…1 Table 1 indicates how these ten theories converge on attitudes, norms, and self-efficacy as major determinants of behavior. Table 1 also contains an entry for intention as most HBTs include intention as a mediator of the influence of attitudes, social norms, and self-efficacy on health CHANGING HEALTH BEHAVIORS 4 behavior, and evidence indicates that intention has a causal impact on behavior (Webb & Sheeran, 2006). Intention is, therefore, considered alongside behavior as an outcome variable in the present review.…”
Section: The Role Of Attitudes Norms and Self-efficacy In Health Bementioning
confidence: 99%
“…Experiments permit the strongest inferences about causality on the basis of three defining characteristics: random assignment of participants to condition, manipulation of the treatment condition, and measurement of the dependent variable (West, Biesanz, & Pitts, 2000; see also Campbell, 1957;Sigall & Mills, 1998). Our metaanalysis leverages these defining characteristics of experiments to generate inferences about the causal role of attitudes, norms, and self-efficacy (see also Sheeran et al, 2014;Webb & Sheeran, 2006). A quantitative review of studies that satisfy the following criteria was conducted: (a) CHANGING HEALTH BEHAVIORS 6 participants are randomly assigned to treatment versus control conditions: Random assignment rules out third variable explanations of the findings as scores on third variables should be evenly distributed between the conditions and thus cannot account for treatment effects; (b) the treatment produces a statistically significant difference in attitudes, norms, or self-efficacy between participants who receive the treatment and control participants: Manipulation of the treatment condition must be successful; change in the putative mediator must occur in order to assess the causal impact of the treatment on the dependent variable.…”
Section: Correlational Versus Experimental Testsmentioning
confidence: 99%
See 1 more Smart Citation